let X be non empty set ; :: thesis: for F, G, H being VECTOR of (C_Algebra_of_BoundedFunctions X)

for f, g, h being Function of X,COMPLEX st f = F & g = G & h = H holds

( H = F + G iff for x being Element of X holds h . x = (f . x) + (g . x) )

let F, G, H be VECTOR of (C_Algebra_of_BoundedFunctions X); :: thesis: for f, g, h being Function of X,COMPLEX st f = F & g = G & h = H holds

( H = F + G iff for x being Element of X holds h . x = (f . x) + (g . x) )

let f, g, h be Function of X,COMPLEX; :: thesis: ( f = F & g = G & h = H implies ( H = F + G iff for x being Element of X holds h . x = (f . x) + (g . x) ) )

assume A1: ( f = F & g = G & h = H ) ; :: thesis: ( H = F + G iff for x being Element of X holds h . x = (f . x) + (g . x) )

A2: C_Algebra_of_BoundedFunctions X is ComplexSubAlgebra of CAlgebra X by Th2;

reconsider f1 = F, g1 = G, h1 = H as VECTOR of (CAlgebra X) by TARSKI:def 3;

then h1 = f1 + g1 by A1, CFUNCDOM:1;

hence H = F + G by A2, Th3; :: thesis: verum

for f, g, h being Function of X,COMPLEX st f = F & g = G & h = H holds

( H = F + G iff for x being Element of X holds h . x = (f . x) + (g . x) )

let F, G, H be VECTOR of (C_Algebra_of_BoundedFunctions X); :: thesis: for f, g, h being Function of X,COMPLEX st f = F & g = G & h = H holds

( H = F + G iff for x being Element of X holds h . x = (f . x) + (g . x) )

let f, g, h be Function of X,COMPLEX; :: thesis: ( f = F & g = G & h = H implies ( H = F + G iff for x being Element of X holds h . x = (f . x) + (g . x) ) )

assume A1: ( f = F & g = G & h = H ) ; :: thesis: ( H = F + G iff for x being Element of X holds h . x = (f . x) + (g . x) )

A2: C_Algebra_of_BoundedFunctions X is ComplexSubAlgebra of CAlgebra X by Th2;

reconsider f1 = F, g1 = G, h1 = H as VECTOR of (CAlgebra X) by TARSKI:def 3;

hereby :: thesis: ( ( for x being Element of X holds h . x = (f . x) + (g . x) ) implies H = F + G )

assume
for x being Element of X holds h . x = (f . x) + (g . x)
; :: thesis: H = F + Gassume A3:
H = F + G
; :: thesis: for x being Element of X holds h . x = (f . x) + (g . x)

let x be Element of X; :: thesis: h . x = (f . x) + (g . x)

h1 = f1 + g1 by A2, A3, Th3;

hence h . x = (f . x) + (g . x) by A1, CFUNCDOM:1; :: thesis: verum

end;let x be Element of X; :: thesis: h . x = (f . x) + (g . x)

h1 = f1 + g1 by A2, A3, Th3;

hence h . x = (f . x) + (g . x) by A1, CFUNCDOM:1; :: thesis: verum

then h1 = f1 + g1 by A1, CFUNCDOM:1;

hence H = F + G by A2, Th3; :: thesis: verum